Еколого-економічні аспекти використання мінеральної сировини у збалансованому розвитку суспільства - Коржнєв, М.М.; Малахов, I.М. (Екологічна безпека та природокористування, 2009)
Environmental and economic aspects of the mineral resources use into balanced development of society have been considered. It is impossible fully to compensate all looses from production activity and reworking of minerals. The way of the people life must radically change under the threat of inevitable casualty.